2015
DOI: 10.3892/or.2015.3858
|View full text |Cite
|
Sign up to set email alerts
|

Repression of engrailed 2 inhibits the proliferation and invasion of human bladder cancer in vitro and in vivo

Abstract: Abstract. Engrailed 2 (EN2) is a member of the homeobox gene family. Many studies suggest that overexpression of EN2 protein may be associated with tumor development, including bladder cancer (BC). However, to date, the mechanisms of how EN2 functions to promote BC progression remain elusive. The present study introduced RNAi to silence the expression of EN2 in BC cell lines. In vitro invasion and migration assays and in vivo experiments were carried out to examine the functions of EN2 in BC invasion and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…We found evidence of novel resistance mechanisms as well, although these findings require prospective validation and functional validation. For instance, EN2 expression may play a role in PI3K pathway activation and PTEN inhibition in bladder cancer cells (44). BRSK2 expression may activate Akt and therefore increase the survival of pancreatic ductal adenocarcinoma cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of novel resistance mechanisms as well, although these findings require prospective validation and functional validation. For instance, EN2 expression may play a role in PI3K pathway activation and PTEN inhibition in bladder cancer cells (44). BRSK2 expression may activate Akt and therefore increase the survival of pancreatic ductal adenocarcinoma cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports confirmed that EN2 contributed to breast cancer as an oncogene (5). More recently, studies have demonstrated that EN2 also plays a role in prostate cancer and BC (6,7). Our previous study indicated that EN2 could activate the PI3K/Akt pathway while inhibiting PTEN as a substitutable cancer gene in BC, and could potentially cure BC in targeted therapies (7).…”
mentioning
confidence: 64%
“…More recently, studies have demonstrated that EN2 also plays a role in prostate cancer and BC (6,7). Our previous study indicated that EN2 could activate the PI3K/Akt pathway while inhibiting PTEN as a substitutable cancer gene in BC, and could potentially cure BC in targeted therapies (7). In addition, the high level of EN2 expression is related to the grade, as well as the stage, of BC in pathology.…”
mentioning
confidence: 99%
“…Recent studies have shown that homeobox-containing genes, including HOX, EMX, PAX, EN, and so on, as key regulators contribute to the development and progression of a variety of human cancers 3 , 18 , 19 . As the human engrailed homolog, EN2 has been reported to correlate closely with human cancers such as prostate, breast, bladder, ovarian cancer, and non -small cell lung cancer 6 – 8 , 20 , 21 . However, it remains unclear whether EN2 has any role in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%